The Effectiveness of Living Things with The Environment Teaching Materials as A Supplement to Improve Scientific Literacy of Junior High School Students - Alimah Alimah; Sri Mulyani Endang Susilowati; Niken Subekti (Universitas Negeri Semarang, 2021)
The ideal science learning reflects the domain of balanced scientific literacy.  Student who have scientific literacy are able to master science material, understand the characteristics of science and be able to recognize the environment through scientific process and apply science concepts in real life.  Based on that statement we developed a research-based teaching materials.  This  study  aims  to analyze  the  effectiveness  and appropriateness of   teaching materials about Interaction  of Living  Things  with  the Environment  for grade  VII. The research method was used Research and Development teaching materials. Data taken in the form of module eligibility was validated by the media and material experts.  Teaching materials effectiveness was analyzed by posttest score, teaching materials characteristics was described by the percentage of teaching materials characteristics based on scientific literacy.  The results showed that the science teaching materials have developed was valid, feasible, and effective to support Interaction of Living Things Learning. It have characteristics based  on  scientific  literacy  and  equipped  with  pictures  to  clarify  the practicum process, completed with observation tables as testing data that could guide students to find the concepts being taught.